Information system design for higher education evaluation based on student's perspective - Tiara Verita Yastica; Muhammad Nashir Ardiansyah; Muhammad Almaududi Pulungan (School of Industrial and System Engineering, Telkom University, 2023)
The quality of Indonesia's higher education institutions has not excelled compared to Southeast Asian countries such as Singapore, Malaysia, and Thailand. Based on 2020 data, the percentage of higher education institutions in Indonesia that have been accredited is 59%. It is crucial to evaluate and improve the factors that affect the quality of higher education institutions based on the student's perspective, the primary customer of higher education institutions. This study aims to evaluate the quality of higher education institutions based on students' satisfaction in real-time. Furthermore, this research will propose a design of an information system that can automate the evaluation process. The findings of this study can be applied to the existing system, providing information and analysis to support the policy-making process.